2020
DOI: 10.24869/psyd.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Abnormal Glucose Metabolism in First-Episode Drug-Naive Schizophrenia

Abstract: Background:Patients with schizophrenia exhibit a higher mortality rate compared with the general population. This mortality has been attributed predominantly by the high risk of type 2 diabetes mellitus in the patients. We aimed to assess the inherent risk of glucose metabolism abnormalities in first-episode drug-naïve schizophrenia.Subjects and methods: We searched English database (PubMed, EMBASE, MEDLINE, Cochrane Library databases) and Chinese database (Wan Fang Data, CBM disc, VIP, and CNKI) from their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…In the second meta-analysis, Yang et al showed that patients at the time of the first episode of schizophrenia, compared to healthy patients, had both higher FG and two-hour values in OGTT, higher fasting insulin activity, and HOMA-IR. It is noteworthy that there were no significant differences in the proportion of HbA 1c [21].…”
Section: Reviewmentioning
confidence: 75%
“…In the second meta-analysis, Yang et al showed that patients at the time of the first episode of schizophrenia, compared to healthy patients, had both higher FG and two-hour values in OGTT, higher fasting insulin activity, and HOMA-IR. It is noteworthy that there were no significant differences in the proportion of HbA 1c [21].…”
Section: Reviewmentioning
confidence: 75%
“…Dysregulation of insulin action has been linked to schizophrenia pathophysiology above and beyond the side effects of pharmacological treatments [1], as shown by the high prevalence of diabetes even before the introduction of antipsychotics in clinical practice [2] and in drug-naïve patients at first-episode psychosis [3]. Although divergent evidence has been reported in the literature [4][5][6][7], a recent meta-analysis showed a significant increase in fasting plasma glucose levels, plasma glucose levels 2 h after an oral glucose load, or insulin resistance in first-episode psychotic patients compared to controls, with heterogeneity across studies likely due to different lifestyles such as diet and smoking, population-specific polymorphisms, and differences in the definition of antipsychotic naïve [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chociaż mechanizm tego zjawiska pozostaje niewyjaśniony, badania sugerują, że osoby ze schizofrenią są podatne na odkładanie się tłuszczu trzewnego, a wynikać to może z wyższych wartości kortyzolu i insuliny u osób z FEP nawet przed włączeniem neuroleptyków, które wraz z nieprawidłową dietą mogą nasilać otyłość centralną [5,8]. Pacjenci z FEP nieleczeni jeszcze lekami przeciwpsychotycznymi mają już zaburzenia metaboliczne, które nie są powiązane z parametrami lipidowymi [9], stwierdza się u nich zaburzenie tolerancji glukozy i wzrost insulinooporności [10,11].…”
Section: Wstępunclassified